Labor Market Matching under Imperfect Information - Tim Willems (Tinbergen Institute, 2010)
Recent research has shown that the standard labor matching model hasdifficulties in reproducing the co-movement patterns observed in US data. Thisis due to the fact that the standard model lacks sufficient propagation of shocks.This paper shows that refining the informational structure of the model leadsto improvements along this dimension: when agents cannot separately identifypersistent and transitory technology shocks on impact (so that they must solvea signal extraction problem), shocks are propagated. Under this specificationthe standard matching model even manages to make recoveries initially jobless,as in the data.
Keywords: D80; E32; J63; J64; 330; imperfect information; labor market matching; signal extraction; jobless growth; Unvollkommene Information; Suchtheorie; Schätzung; USA